2022
DOI: 10.3389/fpubh.2022.854772
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Profile Analysis of Chinese Physicians' Workload Tethered to Paperwork During Outpatient Encounters

Abstract: BackgroundPhysician dissatisfaction with more time spent on related paperwork but less time available for direct interaction with patients is increasing internationally. Increased physician workload resulting from paperwork might negatively affect their interaction with patients and increase the risk for burnout. This study aimed to investigate the level of physician workload tethered to paperwork during outpatient encounters and explore its latent workload subgroups among Chinese physicians.MethodsA cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[21] Study of outpatient doctors' workload in China found that 38.04% of the doctors' service time of each patient in a 4-minute outpatient visit was spent on paperwork (such as taking medical records, writing prescriptions, etc.). [32] We observed that the reimbursement process, while bringing convenience to outpatients with cancer, also sacri ces the physicians' time that should be devoted to medical care. Accordingly, we found that only 22 of the 488 established patients visited the oncologist for symptom control, with each visit lasting approximately 7 minutes.…”
Section: Discussionmentioning
confidence: 94%
“…[21] Study of outpatient doctors' workload in China found that 38.04% of the doctors' service time of each patient in a 4-minute outpatient visit was spent on paperwork (such as taking medical records, writing prescriptions, etc.). [32] We observed that the reimbursement process, while bringing convenience to outpatients with cancer, also sacri ces the physicians' time that should be devoted to medical care. Accordingly, we found that only 22 of the 488 established patients visited the oncologist for symptom control, with each visit lasting approximately 7 minutes.…”
Section: Discussionmentioning
confidence: 94%
“…The reimbursement procedure places serious time demands on clinicians because their time is devoted to completing paperwork as opposed to direct patient care [ 25 ]. A study from China found that 38.04% of the four-minute outpatient consultation time was spent on paperwork [ 26 ]. We observed that the reimbursement process, while bringing convenience to outpatients with cancer, also sacrifices the physicians' time that should be devoted to medical care.…”
Section: Discussionmentioning
confidence: 99%